2007
DOI: 10.1007/s11060-007-9340-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer leptomeningeal metastasis—the role of multimodality treatment

Abstract: Intravenous chemotherapy and, independently, intrathecal chemotherapy improve survival in breast cancer patients with LM. Radiotherapy has a positive impact on the quality of life due to the alleviation of neurological symptoms. The role of radiotherapy in prolonging survival is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 22 publications
4
85
3
4
Order By: Relevance
“…Therapeutic approaches include intrathecal chemotherapy (mainly with methotrexate), radiotherapy of the meninges, systemic chemotherapy with drugs that penetrate the CSF, and surgery to relieve increased intracranial pressure. 5 A recent study has shown that systemic chemotherapy, intrathecal chemotherapy, and whole brain radiation all have a positive impact on patient survival, while radiotherapy of the spinal meninges does not influence patient survival time. While radiotherapy and intrathecal chemotherapy were once the mainstays of LC treatment, systemic chemotherapy (utilizing drugs that can penetrate the subarachnoid space) is gaining popularity as a therapeutic option, as it treats both the meningeal carcinomatosis as well as the systemic malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic approaches include intrathecal chemotherapy (mainly with methotrexate), radiotherapy of the meninges, systemic chemotherapy with drugs that penetrate the CSF, and surgery to relieve increased intracranial pressure. 5 A recent study has shown that systemic chemotherapy, intrathecal chemotherapy, and whole brain radiation all have a positive impact on patient survival, while radiotherapy of the spinal meninges does not influence patient survival time. While radiotherapy and intrathecal chemotherapy were once the mainstays of LC treatment, systemic chemotherapy (utilizing drugs that can penetrate the subarachnoid space) is gaining popularity as a therapeutic option, as it treats both the meningeal carcinomatosis as well as the systemic malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous systemic chemotherapy is preferred in patients who have multiple nodules or MRI evidence of leptomeningeal enhancement, and intrathecal chemotherapy is preferred in patients with positive CSF cytology but negative MRI scans. 5 Aggressive treatment is unlikely to improve neurologic symptoms in many patients; indeed, neurologic toxicity can result, instead. In these patients, palliation may be the best option.…”
Section: Discussionmentioning
confidence: 99%
“…Brain parenchymal metastases can be observed in 21-82% of MC. [34][35][36][37] Any stimulation of the pia mater, such as subarachnoid blood, infection and cancer can produce enhancement of MRI. Lumbar puncture itself can induce a meningeal reaction resulting in leptomeningeal enhancement, so it would be better to conduct MRI examination prior the procedure.…”
Section: Neurological Imagingmentioning
confidence: 99%
“…Conventional systemic treatment has variable penetration in the subarachnoid space depending upon the extent of the breakdown of the BBB due to tumor implants and the subjacent inflammatory phenomenon. Regardless of the BBB drug penetration, data shows that systemic chemotherapy response has a positive impact on the survival of patients with MC 55 . A randomized trial compared intrathecal and systemic chemotherapy with systemic treatment alone in breast cancer patients with MC.…”
Section: Treatmentmentioning
confidence: 99%